O Papel das organizações do terceiro setor na reabilitação psicossocial de pessoas com doença mental : https://doi.org/10.60543/ts_iss.vi9.10797 ("Temas Sociais" Journal, 2025)
The aim of the study was to analyze the role of third sector organizations in the psychosocial rehabilitation of people with mental illness in the context of community intervention in mental healthcare. The methodology is qualitative, using semi-structured interviews and categorical content analysis. Representatives from five organizations in Portugal participated in the study. The results show the relevance of community organizations in psychosocial rehabilitation and social inclusion, through training programs, socio-professional qualification and social support.
Keywords: Mental health. Psychosocial rehabilitation. Third sector. Social work.